Normal contact stiffness identification-based force compensation for a hardware-in-the-loop docking simulator. (4th March 2018) - Wang, Qian; Qi, Chenkun; Gao, Feng; Zhao, Xianchao; Ren, Anye; Hu, Yan
Abstract: Docking is a very important and challenging space operation. To ensure the safety and reliability of the docking, the thorough ground verification is necessary. Hardware-in-the-loop (HIL) simulation is a good choice, especially when the geometric structure of the docking device is complex. However, the HIL simulation suffers from energy increase and instability since time delay in the system is unavoidable. In this study, a six degree-of-freedom (DOF) parallel robot is used as the motion simulator to physically perform the contact in the simulation. To achieve system stability and high fidelity, a normal contact stiffness identification-based force compensation method is proposed. The contact force is compensated through identifying the time-varying stiffness along the normal direction of the contact surface. The 6-DOF force-moment compensation algorithm for the HIL parallel robot system is presented in detail. Simulations and experiments are both carried out, and the results show that the proposed compensation method is effective. Abstract :